Geopolitical Influences in Indonesia’s Nickel Industry - Mulyono, Ainul Mutmainnah; R. Dudy Heryadi; Akim (Ilomata International Journal of Social Science, 2025)
This study analyzes Indonesia's strategic role in the global nickel industry and its implications for geopolitical dynamics, particularly in the context of the rivalry between the United States and China in the electric vehicle battery sector. Despite its possession of the world's largest nickel reserves, Indonesia faces considerable challenges due to domestic policies, including the prohibition of nickel ore exports and the preponderance of Chinese investment. The enactment of the U.S. Inflation Reduction Act (IRA) has further exacerbated the already complex situation in Indonesia by imposing restrictions on subsidies for battery materials, thereby limiting their availability to those sourced exclusively from official U.S. trading partners. This research utilizes a qualitative approach and a literature study to reveal that the Republic of Indonesia is currently confronted with a complex geopolitical dilemma. It is imperative to implement a hedging strategy to ensure the maintenance of balanced relations with both major powers while concurrently expanding strategic partnerships with other nations. The findings offer policy insights that could be used to strengthen Indonesia's role in the global clean energy supply chain.